2011
DOI: 10.4317/medoral.17053
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant bone mechanobiology. Review of the literature

Abstract: The mechanical load applied during bone regeneration in implant treatments influences the early formation of peri-implant bone tissue through the activation of different pathways. The aim of this review was to determine the currently available scientific evidence in this field. Results: There is scientific evidence that the immediate application of an axial load in implantology stimulates bone formation, as measured by various histomorphometric parameters. Different physiological mechanisms (e.g., production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Leucht et al reported that an enhanced osteoblastic differentiation was observed in the early loaded group in the peri-implant tissue [14]. Implantation surgery, as well as the presence of prosthetic loading, might alter the mechanobiology of the peri-implant bone, causing a different reaction to the loading than the bone without an implant [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…Leucht et al reported that an enhanced osteoblastic differentiation was observed in the early loaded group in the peri-implant tissue [14]. Implantation surgery, as well as the presence of prosthetic loading, might alter the mechanobiology of the peri-implant bone, causing a different reaction to the loading than the bone without an implant [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that aging and estrogen removal cause dysregulation in the mechanical control of bone (re)modeling, resulting in decreased sensitivity to mechanical stimulation . There are also concerns that implantation surgery as well as the presence of the implant may alter the mechanobiology of peri‐implant bone, causing a different response to mechanical loading than bone without an implant …”
Section: Effect Of Mechanical Loading On Bone Regenerationmentioning
confidence: 99%
“…18,19 There are also concerns that implantation surgery as well as the presence of the implant may alter the mechanobiology of peri-implant bone, causing a different response to mechanical loading than bone without an implant. 25 This section summarizes recent efforts to understand peri-implant bone behavior following in vivo controlled mechanical stimulation in small animal models ( Table 2). Three different modalities to administer mechanical loading are considered: (i) loading applied directly to the implant (Fig.…”
Section: Effect Of Mechanical Loading On Bone Regenerationmentioning
confidence: 99%
See 2 more Smart Citations